Drama techniques in language learning : a resource book of communication activities for language teachers - Maley, Alan, 1937-; Duff, Alan, 1942- (New York : Cambridge University Press, 1982)
A collection of drama techniques for teaching communication that includes 150 fluency practice ideas and instructions for teachers; covers observation, interpretation, creation and invention, wordplay, problem solving, and the use of literary texts, poems, and songs.
Includes bibliographical references (p. 232-234).
Professional.
Professional
Keywords: Drama in education; Languages, Modern -- Study and teaching; Drama in education; Modern languages -- Study and teaching